The Relationships Among Language Learning Strategy, Motivation, Anxiety and Autonomy in Chinese EFL Learners - Jianfeng, Cheng; Sagaya Raj, Gerard; Tan Tjin Ai, Joanna (International Journal of Engineering and Technology, 2018)
This study attempted to explore the relationships among language learning strategy, motivation, anxiety and learner autonomy. Cluster sampling method was adopted to select 600 non-English major students as subjects at three universities in Henan province, China. Quantitative data collected from questionnaires was analyzed by SPSS 19.0. Results from Pearson correlation analysis showed that among the three investigated variables, language learning strategy and motivation had a significant positive relationship with learner autonomy in a decreasing order, but anxiety was significantly and negatively correlated with learner autonomy. Results from multiple regression analysis indicated that learning strategy could best significantly predict the variance of learner autonomy, followed by motivation and anxiety. The findings would make suggestions to university policy-makers, English language lecturers, and learners on the implementation of autonomous English language learning.Â Â